1998
DOI: 10.1073/pnas.95.25.14843
|View full text |Cite
|
Sign up to set email alerts
|

Stream biodiversity: The ghost of land use past

Abstract: The inf luence of past land use on the presentday diversity of stream invertebrates and fish was investigated by comparing watersheds with different land-use history. Whole watershed land use in the 1950s was the best predictor of present-day diversity, whereas riparian land use and watershed land use in the 1990s were comparatively poor indicators. Our findings indicate that past land-use activity, particularly agriculture, may result in long-term modifications to and reductions in aquatic diversity, regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
659
4
18

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 854 publications
(699 citation statements)
references
References 31 publications
18
659
4
18
Order By: Relevance
“…Conflicting results may in some cases be explained by the difficulties of separating present-day LAND USE AND NUTRIENT EFFECTS ON FRESHWATER BIODIVERSITY from historical influences (Allan, 2004). As Harding et al (1998) clearly showed, the effect of past land use changes can have a major influence on the present-day fish species in rivers and streams. It was not possible to take historical changes into account in this study, as it was dependent on the information given in the articles used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conflicting results may in some cases be explained by the difficulties of separating present-day LAND USE AND NUTRIENT EFFECTS ON FRESHWATER BIODIVERSITY from historical influences (Allan, 2004). As Harding et al (1998) clearly showed, the effect of past land use changes can have a major influence on the present-day fish species in rivers and streams. It was not possible to take historical changes into account in this study, as it was dependent on the information given in the articles used.…”
Section: Discussionmentioning
confidence: 99%
“…Upper and lower confidence levels (95%) are depicted in dashed lines. Data are based on studies by Harding et al, 1998;Sponseller et al, 2001;Collier and Quinn, 2003;Harding, 2003;and Bruns, 2005. This study shows that altered catchment land use can have a major effect on freshwater taxon diversity and that the rate of species loss is serious; from the literature reviewed, every 10% of lost natural catchment land cover led to an average loss of almost 6% ( AE 0.83) of the native freshwater fish and macroinvertebrate species. Quantifying relationships makes it possible to emphasize to policy makers the consequences of continued habitat alteration and eutrophication, and to visualize the costs of these actions in terms of taxon diversity loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, physical alterations caused by agriculture can generate biological impacts over decades (Harding et al, 1998). Other authors have found less negative effects (Meador & Goldstein, 2003), or even positive relationships between agricultural land cover and invertebrate diversity (Moore & Palmer, 2005).…”
Section: Hierarchy Of Impacts: Urbanization Vs Agriculturementioning
confidence: 99%